Proses Manufaktur Mata Pisau Mesin Hummer Mill Penepung Ikan dengan Kapasitas 200 kg/jam - Lubis, Wilmansyah; Darianto, Darianto; Iswandi, Iswandi (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
A hammer mill is a machine that grinds both grains and stones into fine particles called flour. The working principle of the hammer mill is that the impact process is carried out by dynamic blades repeatedly so that it breaks into small particles. The hammer mill consists of dynamic blades mounted on a rotating shaft under which there is a screen that controls the maximum particle size to exit the grinding chamber from within the hummer mill. In the process of making a hummer mill machine there are several problem formulations. One of these problems is the hummer mill machine manufacturing process and the influence of rotation variations on the hummer mill machine. so in this case the author tries to make a machine to achieve this problem, where the hummer mill machine can maximize efficiency in order to achieve more effectiveness. The advantages of this machine, besides being able to grind animal feed, can also grind rocks in the form of fine grains using a 3 mm or 5 mm sieve, which means more efficient 2 uses are needed. while the cost of making this machine does not have to be expensive but affordable, this hummer mill machine can produce a production capacity of 200 kg/hour.